HE INFLUENCE OF GREEN ACCOUNTING, CORPORATE EMISSION DISCLOSURE AND CORPORATE ENVIRONMENTAL GOVERNANCE AS A MODERATOR - Sofwan Hidayah, Muhammad; Sri Lastanti, Hexana (Universitas Islam Lamongan, 2024)
This study aims to determine and find empirical evidence regarding the Influence of Green Accounting, Corporate Emission Disclosure and Corporate Environmental Performance on Financial Performance with Corporate Governance as a Moderator. This study uses secondary data with data collection techniques using financial and annual reports of energy sector companies listed on the Indonesia Stock Exchange (IDX) for the period 2021-2023. This study uses a purposive sampling technique with a total sample of 96 from 32 companies. Data testing in this study uses multiple linear regression analysis. The results of the study indicate that Green accounting has a negative and significant effect on financial performance. Carbon emission disclosure has a positive and significant effect on financial performance. Corporate environmental performance does not have a significant effect on financial performance. Corporate governance weakens the effect of green accounting on financial performance, Corporate governance strengthens the effect of carbon emission disclosure on financial performance. Corporate governance is unable to moderate the effect of corporate environmental performance on financial performance, Corporate Governance of the company is unable to moderate the effect of Corporate environmental on financial performance.